Analisis Manajemen Konstruksi Jembatan Cisumengka Jalan Bebas Hambatan Cileunyi Sumedang Dawuan (Cisumdawu) Tahap III - Sugiyanto, Martinus Agus (Jurnal Civil Engineering Study, 2022)
Construction management is the study and practice of managerial and technological aspects of the construction industry. Construction management can also be interpreted as one of the business capitals carried out by construction consultants in providing advice and assistance in a development project. The Construction Management Association of America “CMAA” states that there are seven main categories of responsibilities for a construction manager. These include project management planning, price management, time management, quality management, contract administration, safety management and professional practice. While the project is a combination of resources such as people, materials, equipment, and costs that are collected in a temporary organization place to achieve a goal and goal. So from the explanation above it can be concluded that project management is the application of knowledge, expertise and skills, the best technical way and with limited resources, to achieve the goals and objectives that have been determined in order to get optimal results in cost performance, quality. , and time, as well as work safety